Penerapan Metode Vogel’s Approximation Method (VAM) dan Modified Distribution (MODI) Dalam Penyelesaian Transshipment Problem - Aisyah Aisyah; Ika Purnamasari; Yuki Novia Nasution (EKSPONENSIAL, 2018)
Transshipment method is an extension of the transportation method. The method of transhipment itself can not be directly to the destination becausethe goodstransported must experience transit, while the method of transporting direct shipment from factory to destination. The data used in this study is data that has been obtained from PT. Nestle Balikpapan Where the data is processed by using the VAM method as a method of initial solution and MODI Method as a Final solution, the data aims to find out whether by using both of methods can reduce operational cost of PT. Nestle Balikpapan and the difference of operational cost before application and after using both of that method. Based on the results of the research can be obtained that by using the Initial Solution Solution with VAM can minimize the cost of 43,54% of the initial cost and continued with the final Solution Method that is MODI for the optimality testing by reduced 44,14%